#### Answer

$P(x)=-x(x-4)(x+3)$
Zeros: $-3, 0, \text{ and } 4$
Refer to the graph below.

#### Work Step by Step

Factor the polynomial completely to obtain:
\begin{align*}
P(x)&=-x(x^2-x-12)\\
&=-x(x-4)(x+3)
\end{align*}
To find the zeros, use the Zero-Product Property by equating each factor to $0$, then solve each equation to obtain:
\begin{align*}
-x&=0 &\text{or}& &x-4=0& &\text{or}& &x+3=0\\
x&=0 &\text{or}& &x=4& &\text{or}& &x=-3
\end{align*}
Use a graphing utility to graph $P(x)$.
Refer to the graph above.